Efek Morfologi Penyisihan Polutan Pada Air Terproduksi Dengan Sistem Lahan Basah Buatan Terhadap Tanaman Typha Latifolia - Aprilya, Sondang Ita; Andrio, David; Elystia, Shinta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Produced water has a complex composition and more than 40% is discharged into the environment. Constructed wetlands is one of the water produced treatment systems that use vegetation, media, and microorganisms for pollutants removal. The objectives of this research were to determine the effect of pollutants removal for Typha Latifolia morfology. Subsurface constructed wetlands is used in this study. The reactor is made with gravel, sand, and soil medium and uses Typha Latifolia as a plant. This research consist of detention time 1,3,5,7,9 day. The experimental result shows that 9 days of detention time, Typha Latifolia has average growth rate 31 cm and weight gain was 0,6 kg.Keywords: Constructed wetland, Subsurface flow, Typha latifolia